2021
DOI: 10.1371/journal.pgen.1009561
|View full text |Cite
|
Sign up to set email alerts
|

DEFECTIVE EMBRYO AND MERISTEMS genes are required for cell division and gamete viability in Arabidopsis

Abstract: The DEFECTIVE EMBRYO AND MERISTEMS 1 (DEM1) gene encodes a protein of unknown biochemical function required for meristem formation and seedling development in tomato, but it was unclear whether DEM1’s primary role was in cell division or alternatively, in defining the identity of meristematic cells. Genome sequence analysis indicates that flowering plants possess at least two DEM genes. Arabidopsis has two DEM genes, DEM1 and DEM2, which we show are expressed in developing embryos and meristems in a punctate p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 75 publications
0
15
0
Order By: Relevance
“…RANGAP1, RCC1, importins, and so on. RAN1 and DEFECTIVE EMBRYO AND MERISTEMS 1 (DEM1) co-localize transiently during meiosis to mediate cell division and gamete viability [49]. In rice (Oryza sativa), OsRAN1overexpressed lines contained more proliferating cells, especially under cold stress, implying a role of RAN1 Because male and female gametophytes develop within multiple layers of somatic cells, imaging mitosis during male and female gametophytic development is challenging, if possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RANGAP1, RCC1, importins, and so on. RAN1 and DEFECTIVE EMBRYO AND MERISTEMS 1 (DEM1) co-localize transiently during meiosis to mediate cell division and gamete viability [49]. In rice (Oryza sativa), OsRAN1overexpressed lines contained more proliferating cells, especially under cold stress, implying a role of RAN1 Because male and female gametophytes develop within multiple layers of somatic cells, imaging mitosis during male and female gametophytic development is challenging, if possible.…”
Section: Discussionmentioning
confidence: 99%
“…RANGAP1, RCC1, importins, and so on. RAN1 and DEFECTIVE EMBRYO AND MERISTEMS 1 (DEM1) co‐localize transiently during meiosis to mediate cell division and gamete viability [49]. In rice ( Oryza sativa ), OsRAN1 ‐overexpressed lines contained more proliferating cells, especially under cold stress, implying a role of RAN1 in mitosis and cell cycle progression [50].…”
Section: Discussionmentioning
confidence: 99%
“…Genome sequence analysis has revealed that dicotyledonous plants such as tomato and Arabidopsis encode two distinct copies of the DEFECTIVE EMBRYO AND MERISTEMS ( DEM ) gene with the DEM1 and DEM2 loci encoding a highly similar protein of unknown biochemical function, except that the encoded proteins interact with RAS-LIKE NUCLEAR PROTEIN (RAN) [ 41 , 42 ]. RAN is conserved in all eukaryotes and plays a fundamental role in nucleus–cytoplasm transport and cell division.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the degree of defective SAM and RAM development in the tomato dem1 mutant resulted in this plant line failing to proceed past cotyledon emergence as part of the seedling stage of early vegetative development [ 41 ]. In contrast to the tomato dem1 mutant, the Arabidopsis dem1 and dem2 single mutants express wild-type-like phenotypes throughout their vegetative development [ 42 ]. However, Arabidopsis plants carrying a single functional copy of the DEM1 gene, and which are homozygous for mutation of the DEM2 gene (specifically, DEM1/dem1 dem2/dem2 plants), showed defects in meiotic cell division and gamete viability [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation